Sterilized Foreign Exchange Market Interventions in a Chartist-Fundamentalist Exchange Rate Model - Robert Schmidt; Timo Wollmershäuser (University of Würzburg, Department of Economics, 2004)
Sterilized foreign exchange market interventions are commonly dismissed by economists as an ineffective policy instrument. Nevertheless many central banks operating under independently floating exchange rates regimes are often engaged in sales and purchases of foreign exchange in order to manipulate the current value of their currencies. In this paper we argue that the skepticism of many economists can be ascribed to their orientation on fundamental-based, efficient-market exchange rate models. Given their weak empirical support, however, it is unreasonable to evaluate the effectiveness of sterilized foreign exchange interventions against the background of this class of models. Therefore, the purpose of this paper is to investigate the effectiveness of sterilized foreign exchange market interventions on the basis of a more suitable model. Using a chartist-fundamentalist model we show that central banks can influence exchange rates by using sterilized interventions. In particular, turning points occur earlier and exchange rate misalignments are substantially reduced.
Keywords: F31; D84; E58; 330; Foreign exchange; central bank intervention; heterogeneous expectation; Wechselkurspolitik; Wechselkurstheorie; Anlageverhalten; Erwartungstheorie; Wertpapieranalyse; Theorie